Transcription Factors behind MYB98 Regulation: What Does the Discovery of SaeM Suggest? - Prakash B. Adhikari; Xiaoyan Liu; Chen Huang; Nobutaka Mitsuda; Michitaka Notaguchi; Ryushiro Dora Kasahara (Plants, 2024)
MYB98 is master regulator of the molecular network involved in pollen tube attraction. Until recently, it was unclear how this gene exhibits exclusively synergid cell-specific expression in ovule. Our recent study has established that a 16-bp-long SaeM element is crucial for its synergid cell-specific expression in ovule, and an 84-bp-long fragment harboring SaeM is sufficient to drive the process. In this study, we have developed a workflow to predict functional roles of potential transcription factors (TFs) putatively binding to the promoter region, taking MYB98 promoter as a test subject. After sequential assessment of co-expression pattern, network analysis, and potential master regulator identification, we have proposed a multi-TF model for MYB98 regulation. Our study suggests that ANL2, GT-1, and their respective homologs could be direct regulators of MYB98 and indicates that TCP15, TCP16, FRS9, and HB34 are likely master regulators of the majority of the TFs involved in its regulation. Comprehensive studies in the future are expected to offer more insights into such propositions. Developed workflow can be used while designing similar regulome-related studies for any other species and genes.